A DESCRIPTIVE STUDY ON TEACHING PRONOUN TO THE FIFTH YEAR STUDENT AT SD N 12 PURWODADI, GROBOGAN IN 2009/2010ACADEMIC YEAR - NURAGUSTIAN, YETTY WORO (2010)
This research paper is intended to describe (1) Curriculum used by the teacher in teaching pronouns, (2) The method used by the teacher in teaching pronouns, (3) The media used by the teacher in teaching pronouns, and (4) System of evaluation used by the teacher in teaching pronouns. This study is a qualitative research. In collecting the data, the writer uses observation, interview and document. The technique of analyzing the data involves (1) Describing the process of teaching pronouns, (2) Discussing the finding of the research, and (3) Drawing conclusion and proposing suggestion. The results of the study show that (1) curriculum used by the teacher in teaching pronoun process is KTSP (school level-based curriculum), (2) The method used by the teacher in teaching pronoun is Grammar Translation Method (GTM), (3) The media used by the teacher in teaching pronouns are board, board marker and the concrete objects in class surrounding in the classroom, and (4) The evaluation system used by the teacher consist of 3 kinds of test: periodical test, mid test and final test. Beside that the teacher takes the evaluation from assignments, homework, and student activity in the classroom.